Respostas
respondido por:
1
-4²+(3-5)*(-2)³-(-2)^4
-16+(-2)*(-8)-16
-32+16
-16
se o -4 inicial estiver sobre parênteses é assim:
(-4)²+(3-5)*(-2)³-(-2)^4
16+(-2)*(-8)-16
16+16-16
16
-16+(-2)*(-8)-16
-32+16
-16
se o -4 inicial estiver sobre parênteses é assim:
(-4)²+(3-5)*(-2)³-(-2)^4
16+(-2)*(-8)-16
16+16-16
16
respondido por:
1
(-4)² + (3-5).(-2)³ - (-2)⁴=
16 + (-2).(-8) - (+16)=
16 + (+16) -16=
16 +16 -16=
16
16 + (-2).(-8) - (+16)=
16 + (+16) -16=
16 +16 -16=
16
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás